CapCut-based instructional video for teaching response text writing to seventh-grade junior high school students - Siti Rukiyah; Missriani Missriani; Desi Agustina Rohmadhawati; Yessi Fitriani (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
The teaching of response text writing in junior high school often faces several challenges, including students’ low motivation, limited use of instructional media, and difficulties in understanding text structure and language features. These conditions highlight the need for innovative learning media that align with students’ characteristics in the digital era. This study aimed to develop and evaluate the feasibility of a CapCut-based learning video for teaching response text writing to seventh-grade students. The research employed a Research and Development (R&D) approach adapted from the Borg and Gall model, simplified into five stages: needs analysis, media design, product development, expert validation, and limited field testing. The participants were 36 seventh-grade students at a junior high school. The media was evaluated by a media expert, a subject-matter expert, and a language expert. Data were collected through observation, interviews, questionnaires, validation sheets, and writing tests, and analysed using descriptive quantitative and qualitative techniques. The results revealed high feasibility scores: 96% from the media expert, 96% from the subject-matter expert, and 92% from the language expert, indicating that the media was highly feasible for instructional use. Student responses were also very positive, with an average score of 88.3%. In addition, students’ writing performance improved significantly, with the average score increasing from 67 on the pretest to 82 on the posttest. These findings demonstrate that the CapCut-based learning video is both feasible and effective in improving students’ response text writing skills and supporting multimodal learning in secondary education.